THE CHALLENGES AND ROLE OF MODERN JOURNALISM IN DIGITAL MEDIA ENTERPRISES - T., Shyam Swaroop (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rise of digital media has revolutionized the landscape of journalism, transforming how news is reported, distributed, and consumed. Traditional journalism is increasingly facing challenges due to the fast-paced, fragmented, and hyper-connected nature of digital platforms. This paper explores the evolving role of modern journalism within digital media enterprises and examines the key challenges that professionals encounter. The paper highlights issues such as the erosion of traditional journalistic values, the influence of algorithms and metrics-driven content, and the pressure to produce real-time news, often compromising on quality. Additionally, it discusses the growing threat of misinformation and the pivotal role of fact-checking in preserving journalistic integrity. The paper also addresses the economic pressures faced by media organizations, particularly the shift towards a revenue model driven by clicks, subscriptions, and advertising, which can undermine editorial independence. Despite these challenges, digital media provides unique opportunities for journalism to become more interactive, accessible, and innovative, fostering new ways of storytelling and engaging audiences. The paper concludes by suggesting strategies to navigate these challenges while preserving the core values of journalism in the digital era.